The Correlation of ELP4-PAX6 With Rolandic Spike Sources in Idiopathic Rolandic Epilepsy Syndromes - Duan, Yiran; Leng, Xuerong; Liu, Chunyan; Qi, Xiaohong; Zhang, Liping; Tan, Wenjun; Zhang, Xiating; Wang, Yuping (Frontiers in Neurology, 2021)
Objective To study the single nucleotide polymorphism rs662702 of ELP4-PAX6 in patients with idiopathic rolandic epilepsy syndromes (IRES) in China and explore the relationship between the distribution of rolandic spike sources and the single nucleotide polymorphism rs662702 in ELP4-PAX6. Methods First, clinical information was obtained from patients diagnosed with IRES. Next, the single nucleotide polymorphism rs662702 of ELP4 was analyzed by using the Sanger method. Resting-state magnetoencephalography data were collected from seventeen patients. We analyzed the epileptic spike sources using the single equivalent current dipole (SECD) model and determined the spike distributions across the whole brain. Finally, Fisher's test was performed to assess the correlation between the single nucleotide polymorphism rs662702 of ELP4-PAX6 and rolandic spike sources. Results ELP4 rs662702 T alleles were found in 10.7% of IRES patients and occurred four times more frequently in these patients than in the healthy controls. TT homozygosity was found in one IRES patient (1.3%), while no TT homozygosity was found in the healthy control group. The IRES rolandic spike sources were unilateral in sixteen patients (94.1%) and were mainly located in the anterior central gyrus (58.8%). The spike source of patients without the ELP4 rs662702 T allele was correlated with the central region (P <0.05). The rolandic spikes sources were significant correlated with the noncentral gyrus (frontal and temporal lobes) in patients with the ELP4 rs662702 T allele (P <0.05). Conclusion The rolandic spike sources of the IRES patients with the ELP4 rs662702 T allele were significantly associated with the noncentral gyrus, including the frontal and temporal lobes. Our study confirmed for the first time in vivo that ELP4 rs662702 T allele overexpression is correlated with the rolandic spike distribution in patients with IRES and provides important insights into how genetic abnormalities can lead to brain dysfunction and into the precise targeting of abnormal discharge sources in the brain.